KEBUTUHAN MASYARAKAT SEKITAR PERUSAHAAN UNTUK PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT PLN (PERSERO) SEKTOR PEMBANGKITAN TARAHAN: KASUS DI DESA RANGAI TRI TUNGGAL KECAMATAN KATIBUNG KABUPATEN LAMPUNG SELATAN - Abdul Mutolib; Sumaryo Gitosaputro; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This study aims to identify and formulate the needs of community around the PT PLN Katibung Sub District in South Lampung District on CSR program.  The research was conducted in the Gotong Royong, Mataram, Sukamaju, and KampungBaru villages of Katibung Sub District, South Lampung District as the locations of implementing CSR programs by PT PLN.  The number of 84 respondents was taken using proportional random sampling.  The analysis methods were quantitative and descriptive qualitative analysis.  The Results showed that: The needs of community around PT PLN included: 1) economy: developing the potential of the village to increase economic activities such as the potential for volcanic rocks in Gotong  Royong and Kampung Baru, marine and tourism potential in Sukamaju, and the potential of using fly ash in the Mataram, 2) social: public health improvement programs either through the establishment of free medical check up or health infrastructure as ‘Puskesdus’in four villages around PT PLN, 3)environmental: sanitation improvement program by widening and deepening gutter of PT PLN to anticipate  flood because of runoff in the Gotong Royong, Mataram, Sukamaju, and Kampung Baru villages. Keywords: CSR, community, needs assesment, program, PT PLN